Safety pharmacology in human pharmaceutical development - Sarazan, R. Dusty (Henry Stewart Talks, 2009)
Adverse functional effects of drugs on vital organ systems have resulted in patient deaths and several product withdrawals over the past two decades, The potential for these effects was not detected in the traditional toxicology studies that were conducted at the time, These unfortunate events have led to the introduction of new international regulatory guidelines and the creation of a new discipline, known as safety pharmacology, which is distinct from toxicology, Safety pharmacology involves experts in pharmacology who specialize in acute adverse effects of potential human drugs, primarily on the cardiovascular, respiratory and central nervous system, These three organ systems have been deemed to be the ones that are acutely critical for life, If safety pharmacology studies had been conducted in the past, according to today's standards, the vast majority of the drugs that resulted in human deaths would never have made it into clinical development, much less therapeutic usage in patients